Exposure to androgen deprivation therapy and risk of anastomotic leakage after colorectal cancer surgery - Rutegård, Martin; Norrgård, Isac; Moshtaghi‐Svensson, John; Hagström, Jaana; Myrberg, Ida Hed; Lantz, Anna; Rasilainen, Suvi; Nordenvall, Caroline; Sund, Malin (Wiley, 2025)
Aim: The risk of anastomotic leakage after colorectal cancer surgery is higher in men, regardless of the anatomical location. Previous studies suggest that this might be due to hormonal differences. The aim of this work was to investigate whether androgen deprivation therapy influenced the incidence of anastomotic leakage.
Method: This is a nationwide registry-based study of men operated on between 2007 and 2021 for colorectal cancer with an anastomosis. Exposure to androgen deprivation therapy (prescribed drugs or surgical castration) was related to anastomotic leakage using mixed-effects logistic regression models. Two control groups were formed: one without and one with prostate cancer but without androgen deprivation. To study the potential target for androgen effect in intestinal tissue, androgen receptor expression was evaluated using immunohistochemistry in a smaller independent cohort to compare receptor expression in relation to leakage.
Results: Some 24 611 men were included in the registry study, of whom 2.4% were exposed to androgen deprivation therapy. In this exposed group, compared with unexposed men with and without prostate cancer, respectively, leak rates were 3.7%, 5.6% and 5.8%, respectively. After adjustment, a nonsignificant reduction of anastomotic leakage in the exposed group was detected (OR 0.70, 95% CI 0.45-1.09) compared with men without prostate cancer. Tissue expression of androgen receptor was very low among patients with and without leakage, albeit with a trend of higher expression among the latter.
Conclusion: Anastomotic leakage rates might be lower in men exposed to androgen deprivation therapy before surgery for colorectal cancer, although this finding must be interpreted cautiously. Effects on anastomotic healing do not seem to be mediated through classical androgen receptor signalling in the intestine.